ANALISIS PENGARUH PERSEPSI KEMUDAHAN TRANSAKSI DAN NILAI PELANGGAN TERHADAP KEPUASAN PENUMPANG KERETA MODA RAYA TERPADU (MRT) JAKARTA - Salis Rabindra Ishaya; Edi Wahyu Wibowo; Yoeliastuti Yoeliastuti (POLITEKNIK LP3I JAKARTA, 2020)
In the era of transportation development and technological sophistication, humans tend to choose transportation that is fast and affordable. The Mass Rapid Transit (MRT) train of Jakarta, has become one of the choices for Jakarta public transportation in its activities. Inaugurated on March 24, 2019, several problems were complained by passengers, namely regarding the perception of ease of transaction and customer value. The Influence of Perceived Ease of Transaction on the satisfaction of passengers of the Mass Rapid Transit (MRT) Train of Jakarta based on statistical results it can be said that Mass Rapid Transit (MRT) Train of Jakarta passengers have partially significant satisfaction to use Mass Rapid Transit (MRT) Train of Jakarta in accordance with the Transaction Ease Perception. Satisfaction with Perception of Ease of Transaction as easy to learn, easy to use, clear, easy to understand, skilled. The Influence of Customer Value on the satisfaction of passengers of Mass Rapid Transit (MRT) Train of Jakarta based on statistical results it can be said that Mass Rapid Transit (MRT) Train of Jakarta passengers have partially significant satisfaction to use Mass Rapid Transit (MRT) Train of Jakarta in accordance with Ticket Prices that have been paid out. Satisfaction of Customer Value paid is due to added value, suitability of costs with benefits, ease of obtaining services, emotional value. The Influence of Perceived Ease of Transaction and Customer Value on the satisfaction of passengers of Mass Rapid Transit (MRT) Train of Jakarta based on statistical results can be said that Mass Rapid Transit (MRT) Train of Jakarta passengers have significant simultaneous satisfaction to use Mass Rapid Transit (MRT) Train of Jakarta in accordance with Ticket Prices, Facilities and Ease of Transaction Ease. The satisfaction of passengers of the Mass Rapid Transit (MRT) Train of Jakarta towards the Perception of Ease of Transaction and Customer Value that are jointly felt are satisfaction of punctuality, satisfaction of completeness of facilities, satisfaction of price suitability, satisfaction of departure schedules, and satisfaction of functions and facilities.Keywords: Mass Rapid Transit (MRT) Train of Jakarta, Facilities, Perception Ease of Transaction, Customer Value